"Mulher Bonita, Onde Vais?": Narrativa Poética E Construção Do Feminino Em Niketche: Uma História De Poligamia, De Paulina Chiziane - Carvalho, Carina De Lima [UNIFESP] (2018)
The Dissertationaimstostudythe Novel Niketche: A Storyofpolygamy, By Paulina Chiziane.Wetryto Observe Towhatextentthefemale Perspective On Its Ownconditionoccurspoeticallyin Thenarrative. For Suchpurpose, Some Of Its Poeticaspects Are Reviewed, Startingfromaninvestigationoftheintraand Extratextual Elementssupporting It. Thereis, Initially, A Mappingandselectionofthemetaphorsandallegoriesexisting In Thetext. Then, Weperformreviewsregardingthe Oral Intertexts In The Novel, Insofar As Thisthemefurtherimpliesaninfluenceonthepoeticityofpaulina's Prose. Wealsointerpretthe Dialogue Occurringbetweentheprotagonistandhermirror, In Ordertoverify In Whichmannersuchelementworks For Theexpressionofthecharacter'ssubjectivityand For Understandingpolygamy As A Cultural Issue.